2021
DOI: 10.1002/essoar.10507930.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geodetic Monitoring at Axial Seamount Since its 2015 Eruption Reveals a Waning Magma Supply and Tightly Linked Rates of Deformation and Seismicity

Abstract: Axial Seamount is a basaltic hot spot volcano with a summit caldera at a depth of ˜1500 m below sea level, superimposed on the Juan de Fuca spreading ridge, giving it a robust and continuous magma supply. Axial erupted in 1998Axial erupted in , 2011Axial erupted in , and 2015 is monitored by a cabled network of instruments including bottom pressure recorders and seismometers. Since its last eruption, Axial has re-inflated to 85-90% of its pre-eruption level. During that time, we have identified eight discret… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Our study models the observed inflation from 2016-2020, during a time when the magma supply rate was initially high, but then waned with time following the 2015 eruption (Chadwick et al, 2022). Given that the magma supply rate is estimated to have varied from >0.1 km 3 /year to <0.01 km 3 /year during that time period (Chadwick et al, 2022), our volume change estimates are reasonable. Mullet & Segall (2022) demonstrated that as the melt fraction of mush in a magma reservoir increases, the deformation caused by a mush-dominated magma storage system is increasingly driven by the overall shape of the mush body, instead of any pressurized melt lens within the mush.…”
Section: Implications For Magma Storage Beneath Axial Calderasupporting
confidence: 60%
See 4 more Smart Citations
“…Our study models the observed inflation from 2016-2020, during a time when the magma supply rate was initially high, but then waned with time following the 2015 eruption (Chadwick et al, 2022). Given that the magma supply rate is estimated to have varied from >0.1 km 3 /year to <0.01 km 3 /year during that time period (Chadwick et al, 2022), our volume change estimates are reasonable. Mullet & Segall (2022) demonstrated that as the melt fraction of mush in a magma reservoir increases, the deformation caused by a mush-dominated magma storage system is increasingly driven by the overall shape of the mush body, instead of any pressurized melt lens within the mush.…”
Section: Implications For Magma Storage Beneath Axial Calderasupporting
confidence: 60%
“…The total volume of the shallow magma storage system beneath Axial was estimated by Arnulf et al (2014) to be 18-30 km 3 and the modeled co-eruptive volume change associated with previous eruptions has been estimated to vary between 0.147 -0.206 km 3 using analytical model source depths of 3-3.8 km (Chadwick et al, 1999(Chadwick et al, , 2012Hefner et al, 2020;. Our study models the observed inflation from 2016-2020, during a time when the magma supply rate was initially high, but then waned with time following the 2015 eruption (Chadwick et al, 2022). Given that the magma supply rate is estimated to have varied from >0.1 km 3 /year to <0.01 km 3 /year during that time period (Chadwick et al, 2022), our volume change estimates are reasonable.…”
Section: Implications For Magma Storage Beneath Axial Calderamentioning
confidence: 83%
See 3 more Smart Citations